A Guo‐shaped patch antenna for hidden WLAN access points. Issue 2 (2nd July 2020) - Chung, Kwok L.; Cui, Aiqi; Feng, Botao
Abstract: This research communication introduces a Chinese‐character artistic antenna, wherein a Guo‐shaped patch antenna is devised for circular‐polarization applications. The novelty is emphasized by Guo‐shaped patch printed in standard SimHei font at the antenna's front end. The artistic patch antenna is singly‐fed and cavity‐backed by a metallic‐box reflector to enhance the forward directivity (~7dBic) and the front‐to‐back radiation ratio (~20 dB). The Guo‐shaped patch exhibits an axial‐ratio bandwidth of 120 MHz that covers the 2.4 GHz band of wireless local‐area network (WLAN) IEEE 802.11b/g/n/ax. The proposed antenna owns an overall dimension of 1λo  × 1λo  × 0.11λo at 2.5 GHz. ©2018 Wiley Periodicals, Inc. Int J RF and Microwave.